1985
DOI: 10.1346/ccmn.1985.0330404
|View full text |Cite
|
Sign up to set email alerts
|

Structural Studies of Nontronites with Different Iron Contents by 57Fe Mössbauer Spectroscopy

Abstract: Abstract--The 57Fe Mrssbauer spectra of a series of untreated and Ca-saturated nontronites showed a predominant Fe a+ resonance which was computer-fitted with two Fe 3 § doublets defining iron in nonequivalent cis-FeO4(OH)2 octahedral sites. In most spectra a doublet indicating tetrahedral Fe 3. was fitted and in one untreated sample a doublet indicating interlayer Fe 3+ was identified. In a further untreated sample the interlayer iron was present as Fe 2+. Upon Ca-saturation the interlayer iron was displaced.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

1986
1986
2007
2007

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 9 publications
2
33
0
Order By: Relevance
“…The linewidth for the inner octahedral Fe 3+ doublet (0.18 mm/s) is rather narrow and is considered to be .~ an artifact of computer-fitting a minor component to the experimental resonance of a disordered structure . The linewidth for the outer octahedral Fe 3+ doublet (0.48 mm/s) is broader .~ than those observed by Cardile and Johnston (1985) -~ for nontronites (0.32 mm/s), but similar in magnitude to those for montmorillonites (Cardile and Johnston, 1986). The broader linewidth serves to indicate that vermiculite and montmorillonite have a similar degree -o of structural disorder resulting from the presence of other octahedral cations (e.g., A13+, Mg~ § These nearest and next-nearest neighbor cations give variety to the type and arrangement of ions about each octahedral = t~ Fe 3 § site and so broaden the octahedral Fe 3+ doublets.…”
Section: Untreated Vermiculitementioning
confidence: 60%
See 1 more Smart Citation
“…The linewidth for the inner octahedral Fe 3+ doublet (0.18 mm/s) is rather narrow and is considered to be .~ an artifact of computer-fitting a minor component to the experimental resonance of a disordered structure . The linewidth for the outer octahedral Fe 3+ doublet (0.48 mm/s) is broader .~ than those observed by Cardile and Johnston (1985) -~ for nontronites (0.32 mm/s), but similar in magnitude to those for montmorillonites (Cardile and Johnston, 1986). The broader linewidth serves to indicate that vermiculite and montmorillonite have a similar degree -o of structural disorder resulting from the presence of other octahedral cations (e.g., A13+, Mg~ § These nearest and next-nearest neighbor cations give variety to the type and arrangement of ions about each octahedral = t~ Fe 3 § site and so broaden the octahedral Fe 3+ doublets.…”
Section: Untreated Vermiculitementioning
confidence: 60%
“…Johnston and Cardile (1985) and Cardile and Johnston ~, (1985), however, showed that nontronite has two nonequivalent cis-octahedral sites. Furthermore, for lowFe montmorillonites, Cardile and Johnston (1986) .z showed that, in accord with electron diffraction evidence (Tsipursky and Drits, 1984), the Fe 3 § is located essentially in the trans-octahedral sites for some sampies.…”
Section: Untreated Vermiculitementioning
confidence: 99%
“…Although nontronite has been studied extensively, it continues to attract a high level of research interest owing primarily to high iron content. The high iron content is suitable for investigation by a wide range of spectroscopic techniques that complements traditional diffraction studies (Goodman et al, 1976;Besson et al, 1983;Cardile and Johnston, 1985;Manceau et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The dominant octahedral cation in nontronites and ferruginous smectite is Fe; and in some nontronites Fe occupies a fraction of the tetrahedral sites (Goodman et al 1976, Cardile 1987, 1989, Cardile and Johnston 1985, 1986, Luca 1991, Luca and Cardile 1989. It is the only major element in the smectite structure that potentially may exist in two relatively stable oxidation states, Fe(II) and Fe(III), and a change in its oxidation state in situ alters the physical and chemical properties of the clay (Stucki 1988, and references therein, Komade1 et al 1990, Stucki and Tessier 1991, Khaled and Stucki 1991, Gates et al 1993.…”
Section: Introductionmentioning
confidence: 99%